Lesson learned on Waste Management with Co-productive Public Services in Community Learning Centers, Tha Muang District, Kanchanaburi, Thailand - Amornsiriphong, Somsak; Mulaphong, Dhanakorn; Chantrawarin, Yuthpong; Koomklang, Jidapa; Phupan, Siwaporn; Rodsoodthi, Shanana; Petchtam, Khemtida; Ratanawijitrasin, Sauwakon (Journal of Ecohumanism, 2024)
Waste management at the community level is a crucial aspect linked to addressing waste issues at various levels—locally, provincially, nationally, and globally. However, effective implementation requires collaboration from various sectors within and outside the community. Collaborative efforts are essential to achieve maximum efficiency. The concept of co-production of public services is an idea that can be successfully applied to waste management. Lesson Learned from award-winning communities in waste management recognized by government agencies overseeing environmental issues, it is evident that the transformation of waste problems in communities is achievable, leading towards the goal of Zero Waste. These communities have successfully turned waste issues into opportunities for learning through community-based learning centers. In these award-winning communities, waste problems have been transformed into valuable lessons by establishing community-based learning centers that utilize the entire community as a learning hub for waste management. These community-based learning centers, totaling nine in number, each create unique lessons in waste management. They serve as community-based learning hubs, providing adaptable solutions that can be effectively applied to various areas. Each learning center contributes to the overall waste management goal but tailors its lessons to suit the specific needs of its community. This adaptability ensures that the lessons learned can be successfully implemented across different regions. The success of these community-based learning centers highlights the potential for a broader application of these waste management strategies, fostering sustainable practices and contributing to the global effort to address waste-related challenges.